Tolerant but facing increased competition: Arctic zooplankton versus Atlantic invaders in a warming ocean - Kaiser, Patricia; Hagen, Wilhelm; Bode-Dalby, Maya; Auel, Holger (Frontiers in Marine Science, 2022)
The Arctic Ocean is rapidly changing. Air temperature is rising two to four times faster in the Arctic than the global average, with dramatic consequences for the ecosystems. Polar zooplankton species have to cope with those increasing temperatures, whilst simultaneously facing increasing competition by boreal-Atlantic sister species advected into the Arctic Ocean via a stronger Atlantic inflow. To assess the sensitivity of Arctic and Atlantic zooplankton to rising temperatures, respiration rates of dominant Arctic species (Calanus hyperboreus, Calanus glacialis, Paraeuchaeta glacialis, Themisto libellula) and their co-occurring Atlantic congeners (Calanus finmarchicus, Paraeuchaeta norvegica, Themisto abyssorum) were measured at ambient temperatures and simulated conditions of ocean warming from 0 to 10°C during three expeditions with RV Polarstern to the Arctic Fram Strait. Arctic zooplankton showed only slowly increasing respiration rates with increasing temperatures, also indicated by low Q10 ratios. In contrast, boreal-Atlantic representatives responded to higher temperatures by a rapid and steeper increase in their respiration rates (higher Q10), suggesting higher metabolic activity. These results imply that Arctic species are physiologically more tolerant to ocean warming than expected but might be outcompeted by their Atlantic congeners beyond a certain temperature threshold in areas of strong distribution overlap. Thus, the ‘Atlantification’ of the Arctic zooplankton community seems to be driven rather by ecological interactions than by physiological limitations. Changes in zooplankton community composition and biodiversity will have major consequences for trophodynamics and energy flux in Arctic ecosystems, since polar species tend to be larger than their southern counterparts and have a higher lipid content, providing more energy-rich food for higher trophic levels.